2024
DOI: 10.3390/toxins16020106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of OnabotulinumtoxinA on Allodynia and Interictal Burden of Patients with Chronic Migraine

Andreas A. Argyriou,
Emmanouil V. Dermitzakis,
Dimitrios Rikos
et al.

Abstract: Background: We primarily aimed to ascertain whether treatment with ΟnabotulinumtoxinA (BoNTA) might influence the extent of the interictal burden and cutaneous allodynia in patients with chronic migraine (CM). Methods: Seventy CM patients, who received three consecutive cycles of BoNTA, were studied. The interictal burden was assessed with the Migraine Interictal Burden Scale (MIBS-4), while cutaneous allodynia was examined with the Allodynia Symptom Checklist (ASC-12) together with PI-NRS VAS to obtain hair b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Our results on ASC-12 parallel those of a previous work on BoNT-A of our group, whose population included the subset of BoNT-A patients of the RAMO study from the Milan centre [ 41 ]. Conversely, other studies showed that BoNT-A in CM can be effective by influencing central sensitisation, by modulating nociceptive drive, and by reducing the overall burden of migraine [ 32 ], and the ASC-12 score decreased significantly in a similar treated population [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results on ASC-12 parallel those of a previous work on BoNT-A of our group, whose population included the subset of BoNT-A patients of the RAMO study from the Milan centre [ 41 ]. Conversely, other studies showed that BoNT-A in CM can be effective by influencing central sensitisation, by modulating nociceptive drive, and by reducing the overall burden of migraine [ 32 ], and the ASC-12 score decreased significantly in a similar treated population [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others described a reduction in the allodynic symptoms in CM using onabotulinumtoxinA. The mechanisms of these preventive treatments could be convergent in reducing the peripheral and central excitability of the trigeminovascular/thalamic relays [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding interictal burden, a recent study conducted on 70 patients treated for three consecutive cycles (nine months) showed a significant reduction of interictal symptoms and cutaneous allodynia, assessed through MIBS-4 and ASC-12. Of interest, interictal burden improvement showed no relations to the persistence of allodynia; the authors concluded that this finding suggests a complex nature of interictal burden, which is not a simple sum of bothersome symptoms and that requires specific instruments to be assessed [77].…”
Section: Effects On Interictal Symptoms and Comorbiditymentioning
confidence: 94%